Sharks of the Open Ocean 2008
DOI: 10.1002/9781444302516.ch4
|View full text |Cite
|
Sign up to set email alerts
|

The Biology and Ecology of Thresher Sharks (Alopiidae)

Abstract: We review the biology and ecology of the three known species of thresher shark (Alopiidae) occurring in the Atlantic, Pacifi c, and Indian Oceans: the common thresher shark (Alopias vulpinus), bigeye thresher shark (A. superciliosus), and pelagic thresher shark (A. pelagicus). We also present revised data on age, growth, and sexual maturity of the common thresher shark off California. These new data suggest that off the US West Coast, male and female common threshers mature at ϳ303 cm total length (TL) and ϳ5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 9 publications
3
47
3
Order By: Relevance
“…The size at maturity obtained in the present study reinforces that the bigeye thresher reaches maturity at a larger size than the other species of the Alopiidae family, as stated by Smith et al (2008a). Assuming that age at maturity is also reached at a later age (Fernandez-Carvalho et al 2011), and considering the very limited fecundity, the reproductive potential of the bigeye thresher is suggested to be very low when compared to other sharks more prevalent in the epipelagic-oceanic areas.…”
Section: Rev Fish Biol Fisheriessupporting
confidence: 89%
See 2 more Smart Citations
“…The size at maturity obtained in the present study reinforces that the bigeye thresher reaches maturity at a larger size than the other species of the Alopiidae family, as stated by Smith et al (2008a). Assuming that age at maturity is also reached at a later age (Fernandez-Carvalho et al 2011), and considering the very limited fecundity, the reproductive potential of the bigeye thresher is suggested to be very low when compared to other sharks more prevalent in the epipelagic-oceanic areas.…”
Section: Rev Fish Biol Fisheriessupporting
confidence: 89%
“…Similarly to the common thresher (Alopias vulpinus) and pelagic thresher (Alopias pelagicus), the litter size of the bigeye thresher is commonly two (rarely four) pups, though they grow more slowly and reach maturity at a later age than the other threshers (Moreno and Morón 1992;Mancini and Amorim 2006;Romero-Caicedo 2007;Smith et al 2008a). In addition, though the bigeye thresher typically occurs in temperate and tropical waters, they can endure colder water and remain longer at deeper waters than many other pelagic sharks (Gruber and Compagno 1981;Smith et al 2008a;IPMA, unpublished data).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Young individuals are often found close inshore and in shallow bays (Compagno et al, 1989;Compagno et al, 2005). Alopias vulpinus is frequently encountered in temperate waters and more common in coastal environments than any of the other thresher sharks (Smith et al, 2008 Type.-Eugaleus omanensis Norman, 1939(Cappetta, 2012.…”
Section: Systematic Paleontologymentioning
confidence: 99%
“…Studies of shark catch rates from commercial fi sheries have found declines of thresher, blue, mako, and oceanic whitetip sharks in the Northwest Atlantic (Baum et al, 2003), although Nakano (1996) found that blue shark catch rates were stable in the Atlantic, as well as in the Pacifi c and Indian Oceans. There is evidence of a decline in an eastern Pacifi c population of common threshers followed by some rebuilding (Smith et al, 2008b). There is evidence of a decline in an eastern Pacifi c population of common threshers followed by some rebuilding (Smith et al, 2008b).…”
Section: Evaluating the Conservation Status Of Open Ocean Sharksmentioning
confidence: 96%